2019
DOI: 10.3390/w11071492
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Climate Change Impacts on Land Surface, Hydrological Processes and Water Management

Abstract: During the last several decades, Earth´s climate has undergone significant changes due to anthropogenic global warming, and feedbacks to the water cycle. Therefore, persistent efforts are required to understand the hydrological processes and to engage in efficient water management strategies under changing environmental conditions. The twenty-four contributions in this Special Issue have broadly addressed the issues across four major research areas: (1) Climate and land-use change impacts on hydrological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Compared to the self-container storage capacity in the sub-catchment, the seven waterlogged places located in No. 5,No.8,and No.20, and the three waterlogged places located in No.19, are not reasonable. The waterlogged places located in No.…”
Section: Discussion On the Storing Ability Of Each Sub-catchment In Tmentioning
confidence: 91%
See 3 more Smart Citations
“…Compared to the self-container storage capacity in the sub-catchment, the seven waterlogged places located in No. 5,No.8,and No.20, and the three waterlogged places located in No.19, are not reasonable. The waterlogged places located in No.…”
Section: Discussion On the Storing Ability Of Each Sub-catchment In Tmentioning
confidence: 91%
“…Furthermore, the storage capacities in No. 5,No.8,and No.20 (in light purple colors) are much higher than the quantity of rainwater.…”
Section: Discussion On the Storing Ability Of Each Sub-catchment In Tmentioning
confidence: 93%
See 2 more Smart Citations
“…Using an equation developed in the study, it was found that climate change awareness positively influences an individual's attitude and intention to reduce the waste that they produce. A fundamental review of the study problems discussed in this research is provided by Zhang and Reggiani, 23 which points out how the performed studies support the improvement of scientific understanding by policymakers. However, all of these solutions only provide theories for the prediction of climate change.…”
Section: Related Workmentioning
confidence: 99%